Controlling the Risk Domain in Pediatric Asthma through Personalized Care - Anderson, William C., III; Szefler, Stanley J. (Seminars in Respiratory and Critical Care Medicine, 2018)
Strategies to control the risk domain of NHLBI EPR-3 (National Heart, Lung, and Blood Institute Expert Panel Report-3) asthma guidelines, which includes exacerbations requiring systemic corticosteroids, reduction in lung growth, and progressive loss of lung function, and treatment-related adverse effects, are evolving in children and adolescents. Increasing evidence demonstrates that children and adolescents with asthma are at risk of a reduction in lung growth, leading to lower lung function and potentially chronic obstructive pulmonary disease as adults. Readily available clinical biomarkers for atopy, including aeroallergen testing, total serum IgE, blood eosinophilia, and spirometry, are being utilized to phenotype difficult-to-treat pediatric patients, to assess risk for seasonal exacerbations, and to predict response to controller therapies. The Composite Asthma Severity Index is a novel, freely available scoring system to define asthma control, incorporating NHLBI EPR-3 risk and impairment domains. As new asthma controller therapies, such as tiotropium, are introduced for pediatric use, the safety of established controller therapies including inhaled corticosteroid and long-acting beta-agonist are being reexamined. Macrolide antibiotics may be an oral corticosteroid sparing alternative for the treatment of severe respiratory tract infection in preschool-aged children. Seasonally directed courses of omalizumab may provide an alternative approach to prevent fall asthma exacerbations in children. Combining these pharmaceuticals and biomarker-directed therapies provide potential new options and personalized approaches to gain asthma control in pediatric patients failing current management.
Keywords: risk domain; lung function decline; biomarker; inhaled corticosteroid; long-acting β-agonist; tiotropium; macrolide; omalizumab